Challenges and perspectives of the Health Technology evaluation agencies in Peru. - Díaz-Vélez, Cristian (2023)
Health Technologies (HT) are important to make appropriate decisions in the field of health. The need to standardize TS evaluations is highlighted, since there are currently differences in the methods and recommendations used. In addition, the lack of trained human resources to carry out these evaluations is mentioned, as well as the long times they can take. Therefore, it is essential to prioritize the technologies to be evaluated to maximize available resources. In Latin America, the health technology prioritization process presents various barriers, such as the lack of an explicit and formal prioritization process in most countries. These barriers include fragmentation of health services, disagreement among stakeholders, and fear of reduced discretion in decision-making. Despite these difficulties, prioritization processes have been developed based on different methodological frameworks, which must be transparent, systematic, efficient, explicit and consensual. Therefore, it is necessary to have reference frameworks to evaluate the impact of these technologies on healthcare. The importance of declaring conflicts of interest in the evaluation of health technologies and how industry influence can affect the evaluation process is highlighted. Furthermore, the need to standardize evaluation methodologies and instruments is highlighted to improve the quality and comparability of STDs.